Targeting Disulfidptosis with Potentially Bioactive Natural Products in Metabolic Cancer Therapy - Xinyan Li; Jiayi Xu; Liangwen Yan; Shenkang Tang; Yinggang Zhang; Mengjiao Shi; Pengfei Liu (Metabolites)
Background: Metabolic cancers are defined by metabolic reprogramming. Although this reprograming drives rapid tumour growth and invasion, it also reveals specific metabolic vulnerabilities that can be therapeutically exploited in cancer therapy. A novel form of programmed cell death, known as disulfidptosis, was identified last year; tumour cells with high SLC7A11 expression undergo disulfidptosis when deprived of glucose. Natural products have attracted increasing attention and have shown potential to treat metabolic cancers through diverse mechanisms. Methods: We systematically searched electronic databases involving PubMed, Web of Science, Gooale Scholar. To ensue comprehensive exploration, keywords including metabolic reprogramming, metabolic cancer, disulfidptosis, natural products and some other words were employed. Results: In this review, we focus on the shared characteristics and metabolic vulnerabilities of metabolic cancers. Additionally, we discuss the molecular mechanisms underlying disulfidptosis and highlight key regulatory genes. Furthermore, we predict bioactive natural products that target disulfidptosis-related genes, offering new perspectives for anticancer strategies through the modulation of disulfidptosis. Conclusions: By summarizing current research progress, this review mainly analyzed the potential mechanisms of natural products in the treatment of metabolic cancer.